2008
DOI: 10.1007/s00415-008-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

The Frontal Assessment Battery (FAB) in Parkinson’s disease and correlations with formal measures of executive functioning

Abstract: The FAB is a useful tool for the screening of executive dysfunction in PD, showing good discriminant and concurrent validities. Normative data provided for the Portuguese version of this test improve the accuracy and confidence in the clinical use of the FAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
111
0
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 23 publications
14
111
0
12
Order By: Relevance
“…Several validation studies have shown that the FAB is sensitive to detecting frontal executive impairment compared with more extensive neuropsychological tests. However, most of these studies were performed on patients with dementia, 20,40,41 and the FAB has not been validated in an OHCA population.…”
Section: Discussionmentioning
confidence: 99%
“…Several validation studies have shown that the FAB is sensitive to detecting frontal executive impairment compared with more extensive neuropsychological tests. However, most of these studies were performed on patients with dementia, 20,40,41 and the FAB has not been validated in an OHCA population.…”
Section: Discussionmentioning
confidence: 99%
“…The Frontal Assessment Battery (FAB; Dubois, Slachevsky, Litvan, & Pillon, 2000 ) is an executive screening test that, over the last years, has become widely used in neurological research (Guedj et al, 2008 ;Lima, Meireles, Fonseca, Castro, & Garrett, 2008 ;Oguro et al, 2006 ;Santangelo et al, 2009 ;Yoshida et al, 2009 ). It consists of six subtests assessing conceptualization, cognitive fl exibility, motor programming, sensitivity to interference, motor inhibitory control, and prehension behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, normative FAB scores for Portuguese subjects have been proposed. The authors evaluated 122 healthy controls using an adapted version of the Brazilian one of the FAB 5 . The aim of the present study was to evaluate the performance of a Brazilian sample of healthy controls on the FAB, correlating their scores to age, gender, schooling and those from the Mini-Mental State Examination (MMSE), as well as to present scores according to the educational level.…”
mentioning
confidence: 99%